Suspek Atresia Bilier Dengan Infeksi Cytomegalovirus dan Malaria : Infeksi Menular Lewat Transfusi Darah? - Mario, Mario; Mashabi, Yasmine; Hairunisa , Nany (Jurnal Biomedika dan Kesehatan, 2024)
Introduction: Blood transfusion can cause infectious complications through transfusion of microbes present in asymptomatic donor blood and/or contamination of stored blood products such as Hepatitis B, Hepatitis C, HIV, syphilis, malaria, Cytomegalovirus (CMV) infection. The risk of infection increases with the amount of blood products transfused.  Case presentation: A 5-month-old boy who had never been to malaria endemic area with jaundice and abdominal enlargement since two months ago, fever since one month ago, and icteric sclera. Data from laboratory results shows anemia, leukocytosis, hyperbilirubinemia, elevated liver enzyme, positive IgM and IgG anti-CMV. Blood smear evaluation:  Trophozoite and ring forms of malaria parasites. Abdominal USG: Type-I Biliary atresia, Choledochal cyst, splenomegaly, ascites, and right pleural effusion. Discussion: An acute Transfusion-transmitted CMV infection in high-risk patients can have severe complications such as billiary atresia, myocarditis, retinitis, encephalitis, or encephalopathy. Leucodepleted blood products for transfusion can reduce the risk of infection. Thick and thin blood smears which is the gold standard for diagnosing malaria, cannot be used for donor screening. Asymptomatic malaria infections may remain undetected. Conclusion: Blood transfusion screening for infectious diseases is still very limited for Hepatitis B, Hepatitis C, Syphilis, and HIV. It is necessary to think about blood transfusion screening for other infectious diseases, such as CMV and malaria, especially in endemic areas, to prevent the occurrence of transfusion-transmitted infection.